Reception study: The omission of narrative text in the English translation of Mo Yan's Life and Death Are Wearing Me Out - Guo, Jiahao; Zou, Deyan (Frontiers in Communication, 2023)
This paper examines the omission of narrative texts in the English translation of Mo Yan's Life and Death Are Wearing Me Out. A textual comparison revealed that the translation contains the radical omission of around 50,000 Chinese characters, comprising nearly 13% of the original text. Since the English version reshapes the original work for an English context and a Western audience, it is worthwhile to examine the consequences of the omissions. In particular, are there any patterns among the omitted sections? Is the version with omissions received more favorably by a Western audience? Omissions of narrative texts and their effects were the focus of this study. The adopted methodology comprises textual analysis, narrative analysis, questionnaire, and interviews. The omissions are explored from six categories: narrative text, descriptive text, embedded text, narrator's comments, characters' monologs and lengthy passages containing multiple omission types. The omission of narrative text and its consequences are the focus of this paper. Through textual and narrative analysis, the discussion identifies discrepancies between the source text and the target text, including mitigation of political criticism, stereotyping of Chinese culture, simplification of narrative structure, and plot reorganization. Through questionnaires and interviews, this paper investigates how the omissions may have influenced the reception of the novel by the target audience. Interestingly, significant omissions of political criticism did not impede Western readers' perceptions of the book's political criticisms. Instead, they facilitate and augment the entertainment aspect of the reading. Therefore, this paper argues that the novel has been rewritten to accommodate a Western audience's reading habits and Western poetological systems and to attract a mass audience.